Comparison of Clinical and Angiographic Profiles of Patients with or without Left Main Coronary Artery Disease - Biswas, Suman Kumar; Mahmood, Manzoor; Sheikh, Naveen; Khaled, Md Fakhrul Islam; Bari, Ahmed Saiful; Abdullah, Abu Sadique; Islam, Rashedul; Ansari, Sanjida; Safiuddin, Mohammad (University Heart Journal, 2022)
Background: Left main coronary artery disease constitutes highest risk lesion subset of CAD population. Flow dynamics and pathophysiology in the left main coronary artery are different from that of the other coronary arteries. So traditional risk factors might interact differently with left main artery resulting in different clinical and angiographic characteristics compared to others. Anatomic pattern evaluation in left main coronary artery disease is important in deciding best management options. However, their pattern and profiles were variably shown in different studies with discrepant Results suggesting geographic variation and lead to evaluation of characteristics in our own population. Better understanding this specific problem might lead to further improvement in its management. Methods: It was an observational cross-sectional study. Ninety-one adult coronary artery disease patients over the period of one year who underwent invasive coronary angiogram were studied. Study subjects were divided into two groups after coronary angiogram: Left main (Group 1) and Non-left main (Group 2) CAD. Demographic data, risk factor profiles and angiographic patterns of both groups were compared to see if any statistically significant difference present or not. Results: The mean age and standard deviation in group 1 is 55.2±9.4 and in group 2 is 55.5±12.9; the comparative analysis showed no statistically significant difference. Most of the patients were male 69 (76%) and the comparative study showed statistically significant differences (p=0.046) which showed left main disease tended to be higher in male. Majority (64%) had BMI in normal range with no significant difference. Among the risk factors comparison, diabetes and family history of CAD showed significant association with the left main cohort (p<0.05). Non-ST elevated ACS was the most common presentation and significantly associated with the left main group (p<0.05). On coronary angiogram, there were 80 patients (87.92%) who had no left main artery involvement while 11 patients (12.08%) had left main disease. The comparative study of coronary artery involvement among the two groups reveals no statistically significant differences (p>0.05) but triple vessel disease was found more commonly than single and double vessel disease. Distal lesions (64%) were found more frequently than other types of left main stenosis followed by ostio-proximal lesion (36%). Conclusion: In the patients with left main coronary artery disease, male gender, diabetes mellitus, positive family history and presentation with non-ST elevation ACS were found to be significantly associated. Distal left main lesion and triple vessel disease were commonly found. University Heart Journal 2022; 18(1): 3-9